THE RELATIONSHIP BETWEEN PEDESTRIAN CHARACTERISTICS AND DENSITY ON JENDRAL SUDIRMAN BATUMERAH STREET - HASANUDIN STREET IN AMBON CITY - Anthoneta Maitimu (Sean Institute, 2023)
The pattern of pedestrian flow shows some similarities to the characteristics of vehicle traffic flow. Due to the close relationship between velocity, flow rate and density, at some stage pedestrian flow will reduce the capacity of existing highways. For this reason, it is necessary to carefully study the movement of flow patterns and characteristics of pedestrians, so that conflicts between pedestrians and vehicles often occur, misuse of the sidewalks used as places to trade. Pedestrians have a weak position when mixing with vehicles. Special JPO for pedestrians. This research was conducted on Jln. General Sudirman Batu Merah - Jl Hasanudin. Observations were carried out for 12 hours. The results of this study can be used as a reference for designing facilities for pedestrians that are not yet contained in the capacity manual.